Wireless Sensor Networks Node Localization-A Performance Comparison of Shuffled Frog Leaping and Firefly Algorithm in LabVIEW - Chandirasekaran D; T. Jayabarathi (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Wireless sensor networks (WSN) have become popular in many applications area including environmental monitoring, military and offshore oil & gas industries. In WSN the sensors are randomly deployed in the sensor field and hence estimation of the localization of each deployed node has drawn more attention by the recent researchers, It’s a unique problem to identify and maximizing the coverage where the sensors need to be placed in a position so that the sensing capability of the network is fully utilized to ensure high quality of service. In order to keep the cost of sensor networks to a minimum, the use of additional hardware like global positioning system (GPS) can be avoided by the use of effective algorithms that can be used for the same. In this paper we attempted to use both the shuffled frog leaping (SFLA) and firefly algorithms (FFA) to estimate the optimal location of randomly deployed sensors. The results were compared and published for the usefulness of further research. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7861